A new variety of Habenaria (Orchidaceae, Habenariinae) from French Polynesia - Margońska, Hanna (Biodiversity: Research and Conservation, 2011)
A new variety of Habenaria tahitensis (Orchidaceae, Habenariinae) from Tahiti and the Marquesas Islands (French Polynesia) is described, illustrated and compared to its closest relatives.